Pertumbuhan dan Hasil Tanaman Mentimun Jepang (Cucumis sativus var Japonese) Akibat Penanaman Tanaman Refugia dan Penjarangan Bunga Mentimun - ragil fatul mardilina; Mahayu Woro Lestari; Siti Muslikah (AGRONISMA, 2022)
Japanese cucumber (Cucumis sativus var Japanese) is a vegetable that belongs to the family Cucurbitaceae (pumpkin plant), which is highly favored by various levels of society. This study aimed to determine the effect of the zinnia flower refugia plant and flower thinning on the growth and yield of Japanese cucumber (Cucumis sativus var Japanese). This research was conducted on 7 February – 7 April 2022 in Kemuning Hamlet, Sukoanyar Village, Pakis District, Malang Regency. In this study using Split Plot Design (Divided Plot Design) with control. The first factor (main plot), planting refugia plants around cucumber plants consisted of 2 levels, namely R0 and R1. The second factor (sub-plots), flower thinning consisted of 5 levels, namely B0, B1 , B2, B3, B4 and B5. There were 11 treatment combinations that were randomly assigned. In each repetition 3 times, with a total of 3 samples so that there were 33 trials with controls. In planting refugia plants and thinning cucumber flowers, the best treatment tendencies were R1B3 on the growth of plant height, leaf area and time of emergence of female flowers. On the yield of fresh weight per fruit and number of fruit per plant the best treatment was R1B1. Then on fresh weight per plant the best treatment was R1B3. Keywords: cucumber plant, refugia plant, flower thinning